A Note on the Use of the Second Vertical Derivative (SVD) of Gravity Data with Reference to Indonesian Cases - Prihadi Sumintadireja; Darharta Dahrin; Hendra Grandis (Journal of Engineering and Technological Sciences, 2018)
Gravity data analysis and interpretation are based, among others, on their spatial variation represented by horizontal and vertical gradients. The gradient or derivative of a gravity field can be calculated either in the spatial domain or the wave-number domain. Historically, the second vertical derivative (SVD) of gravity data can be used to delineate the boundaries of anomalous sources. This paper addresses inappropriate use of the SVD of gravity data, with reference to current practices in Indonesia. The SVD's relative magnitude along a profile is widely used to define whether a density contrast and its dipping orientation correspond to a normal or reverse fault, which may be geologically incorrect. Furthermore, the SVD is calculated by approximation using the horizontal derivative, which may be erroneous especially with poorly distributed data and anomalous 3D sources. We exemplify our analysis with synthetic data and propose a more appropriate spectral-based analysis using field data.